Comparative transcriptome analysis on drought stress-induced floral formation of Curcuma kwangsiensis. (31st December 2022) - Feng, Xin; Zhou, Liying; Sheng, Aiwu; Lin, Ling; Liu, Huicheng
ABSTRACT: The rhizomes and tubers of Curcuma kwangsiensis have extensive medicinal value in China. However, the inflorescences of C. kwangsiensis are rarely known in horticulture, because of its low field flowering rate. In order to improve the flowering rate of C. kwangsiensis, we conducted drought stress treatment on the rhizome of C. kwangsiensis . The flowering rate of rhizome was the highest after 4d of drought stress treatment, and the buds on the rhizome could be obviously swell on the 4th day of rehydration culture. In order to identify the genes regulating the flowering time of Curcuma kwangsiensis, comparative transcriptome analysis was performed on the buds on rhizomes before drought stress treatment, 4 d after drought stress treatment and 4 d after rehydration culture. During this process, a total of 20 DEGs controlling flowering time and 23 DEGs involved in ABA synthesis and signal transduction were identified, which might regulate the flowering of C. kwangsiensis under drought stress. Some floral integration factors, such as SOC1 and FTIP, were up-regulated under drought stress for 4 d, indicating that C. kwangsiensis had flowering trend under drought stress. The results of the present study will provide theoretical support for the application of Curcuma kwangsiensis in gardening.